Evaluation of the elderly' falls efficacy by their status of having a home accident and daily life activities - Şahin, Hande; Erkal, Sibel (Journal of Human Sciences, 2017)
A total of 600 older persons from Cebeci district, Ankara province have participated in this study which aimed to evaluate the elderly' falls efficacy by their status of having an accident and daily life activities. Modified Falls Efficacy Scale (MFES), and Katz Daily Activities Scale were used as data gathering tools in this study. The data were analyzed using standard deviation, arithmetic mean, and the student's t-test to compare the two groups, and the analysis of variance in comparison of multiple groups. The results showed that the falls efficacy scores of the older adults who had experienced a home accident within the past year ( =69,15) were lower than those who had not ( =84,33). The falls efficacy scores of the participants decreased with increased dependence in bathing, sitting/standing, toilet, walking, cooking, cleaning and shopping activities. The participants who were older, had lower educational attainment, low monthly income and green cards, and lived with their relatives had lower falls efficacy scores (p<0.05).